Proposal for upgrading the Greencastle Propagation Station - Barbeau, Gerard (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2017)
The Ministry of Agriculture of Antigua and Barbuda, requested technical assistance in upgrading the Greencastle Propagation Station to IICA and CARDI. The study covered infraestructure and equipment including water supplies; nursery management; technology (reference, techniques, research and demonstration); germplasm improvement; training; guidelines for budgeting, workplan and nursery standards for the release of plants; and implementation schedule and cost sharing. The table of contents presents an analysis of the present situation; a proposal to upgrade the Greencastle Propagation Station; and scheduling and funding of operations.